Rehabilitasi Respirasi pada Pasca Operasi Angkat Pita Suara - Siti Chandra Widjanantie (Syntax Corporation Indonesia, 2024)
Laryngectomy is a surgery that involves the removal of components of the larynx and vocal cords, with a permanent stoma created in the neck. Voice, breathing, and eating functions will be impaired in the long term. After laryngectomy, people lose not only their voice and ability to communicate but also part of their personality. Voice rehabilitation becomes essential in treatment, focusing on acceptable voice production and aspiration prevention and improving the quality of life of larynx-impaired patients post vocal cord removal. Rehabilitation of laryngectomized patients is a current therapeutic challenge. A therapeutic respiratory rehabilitation was designed to meet patient expectations better.